CSF1R inhibition with emactuzumab in locally advanced diffuse-type tenosynovial giant cell tumours of the soft tissue: a dose-escalation and dose-expansion phase 1 study. Issue 8 (August 2015) - Cassier, Philippe A; Italiano, Antoine; Gomez-Roca, Carlos A; Le Tourneau, Christophe; Toulmonde, Maud; Cannarile, Michael A; Ries, Carola; Brillouet, Anne; Müller, Claudia; Jegg, Anna-Maria; Bröske, Ann-Marie; Dembowski, Markus; et al.
Summary: Background: Diffuse-type tenosynovial giant cell tumour (dt-GCT) of the soft tissue (alternatively known as pigmented villonodular synovitis), an orphan disease with unmet medical need, is characterised by an overexpression of colony-stimulating factor 1 (CSF1), and is usually caused by a chromosomal translocation involving CSF1. CSF1 receptor (CSF1R) activation leads to the recruitment of CSF1R-expressing cells of the mononuclear phagocyte lineage that constitute the tumor mass in dt-GCT. Emactuzumab (RG7155) is a novel monoclonal antibody that inhibits CSF1R activation. We have assessed the safety, tolerability and activity of emactuzumab in patients with Dt-GCT of the soft tissue. Methods: In this phase 1, first-in-human dose-escalation and dose-expansion study, eligible patients were aged 18 years or older with dt-GCT of the soft tissue with locally advanced disease or resectable tumours requiring extensive surgery, an Eastern Cooperative Oncology Group performance status of 1 or less, measurable disease according to Response Evaluation Criteria In Solid Tumors version 1.1, and adequate end-organ function. Patients with GCT of the bone were not eligible. Patients received intravenous emactuzumab at 900 mg, 1350 mg, or 2000 mg every 2 weeks in the dose-escalation phase and at the optimal biological dose in a dose-expansion phase. The primary objective was to evaluate the safety and tolerability of emactuzumab, and to determine the maximum tolerated dose or optimal biological dose. All treated patients were included in the analyses. Expansion cohorts are currently ongoing. This study is registered withClinicalTrials.gov, numberNCT01494688 . Findings: Between July 26, 2012, and Oct 21, 2013, 12 patients were enrolled in the dose-escalation phase. No dose-limiting toxicities were noted in the dose-escalation cohort; on the basis of pharmacokinetic, pharmacodynamic, and safety information, we chose a dose of 1000 mg every 2 week for the dose-expansion cohort, into which 17 patients were enrolled. Owing to different cutoff dates for safety and efficacy readouts, the safety population comprised 25 patients. Common adverse events after emactuzumab treatment were facial oedema (16 [64%] of 25 patients), asthenia (14 [56%]), and pruritus (14 [56%]). Five serious adverse events (periorbital oedema, lupus erythematosus [occurring twice], erythema, and dermohypodermitis all experienced by one [4%] patient each) were reported in five patients. Three of the five serious adverse events—periorbital oedema (one [4%]), lupus erythematosus (one [4%]), and dermohypodermitis (one [4%])—were assessed as grade 3. Two other grade 3 events were reported: mucositis (one [4%]) and fatigue (one [4%]). 24 (86%) of 28 patients achieved an objective response; two (7%) patients achieved a complete response. Interpretation: Further study of dt-GCT is warranted and different possibilities, such as an international collaboration with cooperative groups to assure appropriate recruitment in this rare disease, are currently being assessed. Funding: F Hoffmann-La Roche.